Variations in the Physico-chemical Parameters of Some 5a and 5b Substituted Barbiturate Derivatives - RAY, RAKESH; HARI KRISHNA, S.; SHARMA, J.D.; LIMAYE, S.N. (Asian Journal of Chemistry, 2010)
The barbiturates are therapeutically used as sedative, hyponotic, anaesthetic and anticonvulsant agents. The trienolmoiety and 5-substituents regulate the biological activity regarding the lypophilicity/hydrophobicity values of barbiturates against their physico-chemical properties.